Traditional Use, Phytochemistry and Pharmacology of Ananas comosus (L.) Merr.(Family Bromeliaceae): An Update - Kumar, Virender; Dureja, Harish; Garg, Vandana (Current Nutrition & Food Science, 2023)
Background: Ananas comosus belongs to the family Bromeliaceae and is commonly known as pineapple, anannas and anannaasa. Objective: The present review gives detailed information about synonyms, geographical distribution, taxonomical classification, cultivation, pharmacognostical and phytochemical profile as well as about therapeutic potential of Ananas comosus. Methods: For the preparation of the manuscript, all the information was collected from scientific engines and databases (Web of Science, Scifinder, Google Scholar, Scopus, PubMed, Wiley Online Library, Taylor & Francis online) using different keywords. Result: Recent studies of A.comosus are based on traditional use, phytochemistry and pharmacology. The nutritional properties of the fruit are well known. The fruit contains various biological active phytoconstituents such as polyphenol compounds, volatile compounds and carotenoids, etc. which are therapeutically active. A.comosus is used for digestive issues, inflammation, seasickness and in a sore throat. Different studies on A.comosus have been conducted due to ethnopharmacological profile. It possesses antimalarial, antidiabetic, abortifacient, anticancer, antioxidant, antidiarrhoeal activity, etc. Finally industrial applications and ongoing clinical trials on pineapple are also summarized. Conclusion: This review would assist researchers in formulating a therapeutically active herbal remedy.
Keywords: phytoconstituents